First Prize for Proposal Maleth/Haven/Port - Antoniou, Klitsa (My University, 2026)
First Prize for Proposal Maleth/Haven/Port: Heterotopias of Evocation Following an open call for an international competition Maleth/Haven/Port was selected to Represent Malta for Venice Biennale 2019.
Keywords: Arts and entertainment